Paradigm to Enhance Thailand Tourism Marketing Development for Japanese Senior Citizens - Duangdao, Yoshida; Na Thalang, Chawalee; Pomsuwan, Suthinan; Tungbenchasirikul, Sahanon (Dusit Thani College Journal, 2020)
The purpose of this research paper is to study the paradigm shifts in the processes of Thai Tourism Market Development and in relation to senior Japanese tourists Methodology Descriptive Qualitative research approach is used in this study and semi-structural questionnaire is used to collect data and assess how the paradigm shifts take place. Study sample consists of 31 individuals representing four groups; namely 1) government agencies, 2) Tourist entrepreneurs in Thailand who provide services for senior Japanese tourists, 3) Local entrepreneurs, and 4) Senior Japanese tourists. The study finds that all the groups tend to coordinate and support each other for developing and promoting their tourism products and services in different work processes. Implications of the study suggests that government agencies working in planning and policy making process are responsible for developing and promoting tourism for senior Japanese tourists in response to the needs of the members of that group. Further, it is found that entrepreneur should come forward, promote and maintain strong public relations with senior Japanese tourists. Plans and programs are needed to implement to assure the quality and safety of products and services before offering them for tourists. Lack of Japanese language skills is also been identified as a major barrier to take off the paradigm shifts. It finds that appropriate training and timely capacity building programs can create value within processes in the tourism industry. In terms of price competitiveness, quality of products, income and employment generation, local entrepreneurs are found to be key aspects in tourism development processes and therefore, tourism products and services can be offered at fair price.